A companion to the classical Greek world - Kinzl, Konrad H., 1940- (Malden, MA : Blackwell Publishing, 2006)
This Companion provides scholarly yet accessible new interpretations of Greek history of the Classical period, from the aftermath of the Persian Wars in 478 B.C. to the death of Alexander the Great in 323 B.C. Topics covered range from the political and institutional structures of Greek society, to literature, art, economics, society, warfare, geography and the environment. Discusses the problems of interpreting the various sources for the period. Guides the reader towards a broadly-based understanding of the history of the Classical Age.
1: The Classical Age as a Historical Epoch -- 2: The Literary Sources -- 3: The Non-Literary Written Sources -- 4: The Contribution of the Non-Written Sources -- 5: Athens, Sparta and the Wider World -- 6: Aegean Greece -- 7: The Central and Northern Balkan Peninsula -- 8: The Greek Cities of the Black Sea -- 9: Western Greece (Magna Graecia) -- 10: Beyond Magna Graecia: Greeks and Non-Greeks in France, Spain and Italy -- 11: The Eastern Mediterranean and Beyond: The Relations between the Worlds of the "Greek" and "Non-Greek" Civilizations -- 12: The Natural Environment -- 13: Environments and Landscapes of Greek Culture -- 14: The Economic Realities -- 15: Religious Practice and Belief -- 16: Citizens, Foreigners and Slaves in Greek Society -- 17: Women and Ethnicity in Classical Greece: Changing the Paradigms -- 18: Greek Government -- 19: Democracy -- 20: Law and Rhetoric: Community Justice in Athenian Courts -- 21: The Organization of Knowledge -- 22: From Classical to Hellenistic Art -- 23: Warfare in the Classical Age -- 24: The Greek World, 478-432 -- 25: The Peloponnesian War and its Aftermath -- 26: The Greek World, 371-336 -- 27: The Conquests of Alexander the Great
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: 5.-4. století př. Kr; starověké Řecko -- dějiny -- 5.-4. století př. Kr; ancient Greece -- history -- 5th-4th centuries B.C.; studie; sborníky; e-knihy online; studies; papers of several authors; e-books online